Rapiña y (des)politización de cuerpos marginalizados y feminizados en tres relatos del realismo social ecuatoriano (Crítica) - Cevallos González, Santiago Andrés (2021)
This investigation into three stories of Ecuadorian social realism, namely, Barranca Grande by Jorge Icaza, Los Sangurimas by José de la Cuadra and El Guaraguao by Joaquín Gallegos Lara, reveals the way in which the mortal remains of their vulnerable and vulnerized characters, and its relation to politics. The analysis and interpretation of these paradigmatic literary texts focuses on looking at the relationship between indigenous, Afro- descendant and female bodies, with the figure of the vulture and the idea of plunder understood in its broadest sense as predation. Based on this relationship, this paper seeks to rethink the literary political proposal of this segment of Ecuadorian literature, for although there is a concern to make visible the violence inflicted on these marginalized bodies, a fundamental limit is discovered when considering the fate of the mortal remains of feminine and feminized bodies.